Personal Non-Property Rights In Copyright (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This annotation explores the concept of personal non-property rights within the framework of copyright legislation in Uzbekistan. The analysis delves into the legal provisions and regulations that govern the protection of personal non-property rights of authors and creators in the realm of intellectual property law. By examining the specific statutes and guidelines outlined in Uzbekistan's copyright legislation, this annotation aims to provide a comprehensive understanding of the rights granted to individuals in relation to their creative works. Additionally, it highlights the significance of safeguarding personal non-property rights as a means of upholding the integrity and dignity of authors while fostering a conducive environment for innovation and artistic expression within the Uzbek legal context.